RETRACTED: Tumor-Derived Extracellular Vesicles Promote Activation of Carcinoma-Associated Fibroblasts and Facilitate Invasion and Metastasis of Ovarian Cancer by Carrying miR-630 - Cui, Yulan; Wang, Deying; Xie, Min (Frontiers in Cell and Developmental Biology, 2021)
Ovarian cancer (OC) is a lethal gynecological malignancy. Extracellular vesicles (EVs) are crucial media in cell-to-cell communication by carrying microRNAs (miRs). The current study aims to investigate the underlying mechanism of miR-630 carried by OC cell-derived EVs in regard to invasion and metastasis of OC cells. miRs related to OC metastasis were searched and screened. The expression patterns of screened miRs in human normal fibroblasts (NFs) and carcinoma-associated fibroblasts (CAFs) were detected using RT-qPCR. miR-630 related to OC metastasis and CAFs activation was analyzed further. The levels of FAP and α-SMA were detected using Western blotting and immunofluorescence. The migration of NFs was measured using Transwell assay. OC cell-derived EVs were isolated and identified. Uptake of EVs by NFs was observed using immunofluorescence staining. The culture supernatant of NFs was collected and used to culture the low metastasis cell line OVCAR8. The migration and invasion of OC cells and epithelial mesenchymal transition (EMT) were measured. Moreover, a xenograft model was established by injecting OVCAR8 cells of different groups into nude mice. Lastly, the effect of EV-pretreated NFs on invasion and metastasis of OC cells was observed in vivo. miR-630 was upregulated in OC cells and CAFs, and further associated with CAF activation and OC metastasis. miR-630 overexpression increased the levels of FAP and α-SMA in NFs, resulting in the transformation of NFs into CAFs. EVs carried miR-630 into NFs and EVs promoted CAF activation. miR-630 targeted KLF6. miR-630 inhibition or KLF6 overexpression attenuated EVs-induced CAF activation. EVs activated the NF-κB pathway via the miR-630/KLF6 axis. The conditioned medium of NFs pretreated with EVs promoted the invasion and metastasis of OVCAR8 cells, while downregulating miR-630 in EVs partially inhibited the promotive effect of NFs. EV-pretreated NFs promoted invasion and metastasis of OC in vivo. In conclusion, EVs carried miR-630 into NFs, thereby facilitating CAF activation and promoting invasion and metastasis of OC by inhibiting KLF6 and activating the NF-κB pathway. Our findings might offer a novel mechanism of invasion and metastasis of OC from the perspective of tumor microenvironment.